Does Threatening Valued Components of Cultural Worldview Alter Explicit and Implicit Attitudes About Death? - Bassett, Jonathan F. (Individual Differences Research, 2005)
The goal of the present study was to test (he hypothesis derived from Terror Management Theory, that cultural worldview acts as a buffer against death anxiety. University students (N = 76) were randomly assigned to read either an essay that described marriage as an antiquated and untenable social institution, an essay that described America's status as world superpower as transitory, or a no threat control essay about the difference between an encyclopedia and a dictionary. Next, all participants completed the revised Death Anxiety Questionnaire and a version of the Implicit Association Test that measured the degree to which they associated death more with self or other people. Worldview threat did not affect participants' explicit death anxiety but participants in the marriage threat condition did show greater implicit death concern than those in the control condition. Implications for future research on Terror Management Theory are discussed. Reprinted by permission of the publisher.